Behavior of an Innovative Square Composite Column Made of Four Steel Tubes at the Corners and Corrugated Steel Batten Plates on all Sides - Chengquan Wang; Zou Yun; Jinxin Kang; Yuan Zhou; Ming Chen; Yichao Wu (Advances in Civil Engineering)
Steel-concrete composite (SCC) columns have widely been applied in modern construction industry owing to the composite action between the concrete and the steel. The benefits of SCC columns can be further achieved if the confinement effect of concrete is applied. Therefore, this paper presents an innovative square steel-concrete composite (ISSCC) column made of four steel tubes at the corners and corrugated steel batten plates on all sides. Through the experimental and finite element (FE) numerical simulation calculations, the axial compression performance and seismic performance of the ISSCC column were discussed, and the FE model was verified through experimental results. The seismic performance of the ISSCC column was compared and analyzed with reinforced concrete column under different axial compression ratios. The research showed that FE models can accurately simulate the deformation, stress, and failure states of the ISSCC column under axial pressure and horizontal low cyclic load. Furthermore, the ISSCC column performed good ductility and energy dissipation capacity, and the seismic performance index was better than the reinforced concrete column and had better seismic performance. The results of this study can provide reference for the design and development of the new composite column.